A caminho da fronteira: entre Heidegger e os japoneses - Teixeira, Luiz Fernando Fontes (2010)
Became a little more than half century ago that has been consolidated the also called philosophy of comparative edge, by which was possible exploited new ways of thought, since the dialogue between West and East. This fructiferous cooperation between-edges, by which possibilities has been ramifies in lots of different areas of knowledge, has a common birthplace: the talk between Heidegger and the Japanese from the also called Kyoto School of Philosophy. The intention of this mastering degree s dissertation is show, since Heidegger s thought and the contemporary Japanese philosophy, the theoric viability of such trade of experiences between westerns and easterns in philosophy.